INTERNALIZATION OF CHARACTER EDUCATION BASED ON LOCAL WISDOM (Field Studies in Kampung Kahuripan / Tajur Pasanggrahan Village of Purwakarta Regency) - Aziz, Helmi (Jurnal Pendidikan Islam, 2016)
The character of Indonesian nation as the friendly, cooperation, deliberation to agree, and modesty nation has been gone because the local wisdom values has been ignored. In this context, the field research is done to see how the society of customas minority groups whom keeping local wisdom values internalized. The society of customin Kampung Kahuripan/ Tajur Pasanggarahan Village of Purwakarta District is still internalizing and keeping the custom values such as keeping conservation, deliberation to agree, cooperation,politeness, and modesty. The process of internalization is through teaching, familiarizing, modeling, motivating and law enforcement so that the character is internalized to all of people in Kampung Kahuripan/ Tajur Pasanggarahan Village of Purwakarta Regency.